Acoustical unmanned aerial vehicle detection in indoor scenarios using logistic regression model. Issue 1 (March 2021) - Iannace, Gino; Ciaburro, Giuseppe; Trematerra, Amelia
In this study, the data obtained from the acoustic measurements were used to train a model based on logistic regression in order to detect a quadrotor's vehicle in indoor environment. To simulate a real environment, we made sound recordings in a shopping center. The sounds related to two scenarios were recorded: only anthropic noise and anthropic noise with background music. Later, we reproduced these sounds in an indoor environment of the same size and characteristics as the shopping center. During the simulation test, a drone placed at different distances from the sound level meter was turned on at different speeds to identify their presence in complex acoustic scenarios. Subsequently, these measurements were used to implement a model based on logistic regression for the automatic detection of the unmanned aerial vehicle. Logistic regression is widely used in pattern recognition of the binary dependent variable. This model returns high value of accuracy (0.994), indicating a high number of correct detections. The results obtained in this study suggest the use of this tool for unmanned aerial vehicle detection applications.